A STUDY OF MATHEMATICS LEARNING ACHIEVEMENT AND SKILLS IN GROUP WORK BY ORGANIZING LEARNING ACTIVITIES BASED ON DAPIC ON MATHEMATICAL SKILLS AND PROCESSES OF MATHAYOMSUKSA THREE STUDENTS - ผิวนวล, จักรพงษ์ (Academic Journal Phranakhon Rajabhat University, 2020)
The purposes of this research were to study mathematics learning achievement and skills in group work of Mathayomsuksa three students by organizing learning activities based on DAPIC on mathematical skills and processes. The target group was 37 students in Mathayomsuksa three students amount 1 classroom at Kasetsart University Laboratory School Center for Educational Research and Development in the second semester of the academic year 2019. The research used three instruments namely; 8 mathematics lesson plans on mathematical skills and processes by organizing learning activities based on DAPIC, mathematics learning achievement test on mathematical skills and processes, and students’ skills evaluation form in group work. Frequency, percentage, mean, and standard deviation were used for analyzing data. The research findings revealed that the mathematics learning achievement on mathematical skills and processes after organizing learning activities based on DAPIC of almost all students passed the 60% criteria which average mark of the overall students was 61.32%. While students’ skills in group work toward organizing learning activities based on DAPIC which assessed by teacher shown that students expressed their behaviors in very good level such as have consultation in group, understand the problem together to analyze the problem, follow methods and procedures for solving the agreed problems, show the result of problem solving correctly and completely, listen to others opinions, work intention, and work finished in time. Whereas behaviors in presenting ideas and methods for solving problem in good level. And the results assessment by students shown that students expressed their behaviors in very good level all behaviors.